(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The current study was designed to check the association of career development with human capital among nurses. The significance of expertise, networking and practice were reviewed with cohort comparison. Utter occupational proficiency had an optimistic impact on nurses’ promotion at the middle and upper job levels. The data was collected from 201 nurses from all Tehsils of district Muzaffargarh using purposive sampling in terms of their qualifications. The structured questionnaire was used to collect data from the nurses, including 157 female nurses and 44 male nurses. The findings indicated the training of human capital in terms of emotional labor, communication, and management skills was related to the career development (p<0.05) of nurses. Health setting and gender were related to the career development (p<0.05) of nurses. In public hospital female nurses were paid more than male nurses, and they were also getting more beneficial allowance in both health care settings, but the opportunity for male nurses was more in private hospitals and for females in public hospitals. There were equal chances of promotion for both genders in both health care settings. The study concluded that career development opportunities were more for female nurses in public hospitals than male nurses who experienced more career development in private sectors of health care.